Five years of experience with ID‐NAT at a tertiary care centre in North India: An interdictory step in preventing the transfusion‐transmitted Infections. (29th February 2016) - Kabita, C.; Poonam, C.; Rahul, C.; Diptiranjan, R.; Kanchan, D.; Parag, F.
Abstract : Introduction: Technological advancements in transfusion medicine have led to safer blood supply to the community like never before. However, blood safety is a daunting task in India with 1.25 billion population and high prevalence rate of HIV (0.29%), HBV (2–8%) and HCV (2%) in donor population. This study aims at evaluating the impact of ID‐NAT as an add‐on test on safe blood supply in the current Indian scenario. Materials and Method: A retrospective observational study was conducted to analyse the data of 5 years of add‐on NAT at Main Blood Bank, AIIMS, New Delhi. Results: 1.84% (3556 of 193 167) units were initially NAT reactive. A total of 3495 units were further tested, of which 79.25% were discriminated (193 HIV, 421 HCV, 2060 HBV and 96 co‐infections). The remaining 13% (456) were repeat non‐reactive and 7.7% (269) could not be discriminated. Overall, NAT yield rate was one in 847, whereas virus‐specific NAT yield rates were one in 96 584, one in 2683, one in 1370 and one in 14 859 for HIV, HCV, HBV and HBV/HCV Co‐infections, respectively. Conclusion: Five‐years of ID‐NAT screening interdicted 228 probable TTIs to 684 (assuming 100% component separation) transfusion recipients. Implementation of NAT along with routine serological tests for screening of the blood donations definitely improves the transfusion safety. However, interpretation of NAT reactive results should be adjudged cautiously keeping in mind, the chance occurrence of false‐positive reactivity.